DIVERSION PICKS DIRECTIONS FOR GROWTH PERFORMANCE SPORTS TO BEAM (GYMNASIUM, 2009)
This paper aims to highlight the requirements of the code's score FI.G. samples "beam" and anumber of specific directions in this device leading to a new approach to the selection process to increasecapacity performance gymnasts.Sample beam is the most demanding test of female gymnastics Allround Speed Skating.The result obtained from this device influence determining the final outcome in the contest or AATeam.